Leptospiral infection: a serosurvey in urban and rural communities in Olavarría county, Argentina - Mariana Alejandra Rivero; Exequiel Alejandro Scialfa; Héctor Mario Appendino; Melina Barbero; Paola Barragán; Félix Carlos Martin; Betsabé Morón; Julia Analia Silva; Adela Tisnés; Silvia Marcela Estein; Marcelo Lisandro Signorini; Silvia Elena González Ayala; et al. (Journal of Infection in Developing Countries)
Introduction: Leptospirosis is a neglected zoonotic disease, affecting mainly poor and vulnerable populations.